Does Warming Enhance the Effects of Eutrophication in the Seagrass Posidonia oceanica? - Pazzaglia, Jessica; Santillán-Sarmiento, Alex; Helber, Stephanie B.; Ruocco, Miriam; Terlizzi, Antonio; Marín-Guirao, Lázaro; Procaccini, Gabriele (Frontiers in Marine Science, 2020)
Seagrasses meadows are disappearing at rates comparable to those reported for mangroves, coral reefs, and tropical rainforests. One of the main causes for their decline is the so-called cultural eutrophication, i.e. the input of abnormal amounts of nutrients derived from human activities. Besides the impact of eutrophication at a local scale, the occurrence of additional factors of stress such as global sea warming may create synergisms in detriment of the seagrass meadows health. In the present study, we aimed to evaluate if plants undergoing chronic cultural eutrophication and plants from relatively pristine sites are more (or less) sensitive to heat stress, nutrient load and the combination of both stressors. To address this question, a mesocosm experiment was conducted using P. oceanica collected from two environments with different nutrients load history. Plants were exposed in controlled conditions to high nutrient concentrations, increased temperature and their combination for 5 weeks to assess the effect of the single stressors and their interaction. Our results revealed that plants experiencing chronic cultural eutrophication (EU) are more sensitive to further exposure to multiple stressors than plants growing in oligotrophic habitats (OL). OL and EU plants showed different morphological and physiological performances, which corroborates the role of local conditions in activating different strategies in response to environmental changes. Plants collected in the eutrophic site appeared to be weaker during the treatments, showing the greatest percentage of mortality, particularly under increased temperature. Temperature and nutrient treatments showed opposite effects when tested individually and an offset response when combined. The activation of physiological strategies with high energetic expense to cope with excess of nutrients and other stressors, could affect plants present and future persistence and survival, particular in the eutrophic site. Our results represent a step forward in understanding the complex interactions that occur in natural environments. Moreover, unravelling intraspecific strategies and the role of local acclimation/adaptation in the response to multiple stressors could be crucial for seagrasses conservation strategies under climate change scenarios.